PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI PENJUALAN TERHADAP LOYALITAS PELANGGAN KOPI JANJI JIWA DI NGANJUK - Sri Riyanti, Anggita; Zulistiani; Purnomo, Hery (Universitas Nusantara PGRI Kediri, 2022)
This research is motivated by the idea of ​​a culinary business (Coffee Shop). This business idea is currently experiencing very rapid development. In addition to its rapid development, of course, the competition is also quite tight. Thus the coffee shop business must be innovative and smart in making its marketing strategy. This study aims to analyze product quality, product prices and product promotions that are carried out partially and simultaneously which affect consumer loyalty at Promise Jiwa Coffee Nganjuk. In this study, a quantitative approach was applied by collecting primary data obtained through a questionnaire. In this study, the population used was Kopi Promise Jiwa customers by taking data samples of 40 respondents. Sampling using non-probability techniques and accidental sampling techniques as an approach and using multiple regression analysis performed using SPSS software. The conclusion obtained from this study is that there is a good influence between quality, price and seller promotion partially on consumer loyalty who consumes Promise Jiwa Coffee in the Nganjuk area.